Research into the Loading of the Tank Car Frame Concept with Filler in the Composite Center Sill - Fomin, Oleksij; Gerlici, Juraj; Lovska, Alyona; Kravchenko, Kateryna (Communications - Scientific Letters of the University of Zilina, 2022)
The study deals with determination of the dynamic loading on the frame of a tank car with closed composite center sill filled with elastic-viscous filler. It has been found that the measures for improvements can decrease the dynamic loading of the frame by 3.5 % in comparison to that of the structure without a filler. The strength calculation of the frame of a tank car is also presented. It was found that the maximum equivalent stresses occurred in the contact area between the center sill and the body bolster; they amounted to about 284.7 MPa and did not exceed the allowable values. The computer modelling of the dynamic loading of the tank car frame was also conducted. The numerical values of accelerations and the distribution fields of accelerations in the frame of a tank car were determined. The results of the calculation showed that the hypothesis on the adequacy was not rejected. The natural frequencies and oscillation modes of the tank car frame were also determined.
Keywords: tank car; frame; center sill; dynamic loading; strength; modal analysis